A Robust Molecular Porous Material for C2H2/CO2 Separation. Issue 11 (21st December 2022) - Gao, Mei‐Yan; Sensharma, Debobroto; Bezrukov, Andrey A.; Andaloussi, Yassin H.; Darwish, Shaza; Deng, Chenghua; Vandichel, Matthias; Zhang, Jian; Zaworotko, Michael J.
Abstract: A molecular porous material, MPM‐2, comprised of cationic [Ni2 (AlF6 )(pzH)8 (H2 O)2 ] and anionic [Ni2 Al2 F11 (pzH)8 (H2 O)2 ] complexes that generate a charge‐assisted hydrogen‐bonded network with pcu topology is reported. The packing in MPM‐2 is sustained by multiple interionic hydrogen bonding interactions that afford ultramicroporous channels between dense layers of anionic units. MPM‐2 is found to exhibit excellent stability in water (>1 year). Unlike most hydrogen‐bonded organic frameworks which typically show poor stability in organic solvents, MPM‐2 exhibited excellent stability with respect to various organic solvents for at least two days. MPM‐2 is found to be permanently porous with gas sorption isotherms at 298 K revealing a strong affinity for C2 H2 over CO2 thanks to a high (Δ Q st )AC [ Q st (C2 H2 ) − Q st (CO2 )] of 13.7 kJ mol −1 at low coverage. Dynamic column breakthrough experiments on MPM‐2 demonstrated the separation of C2 H2 from a 1:1 C2 H2 /CO2 mixture at 298 K with effluent CO2 purity of 99.995% and C2 H2 purity of >95% after temperature‐programmed desorption. C‐H···F interactions between C2 H2 molecules and F atoms of AlF6 3− are found to enable high selectivity toward C2 H2, as determined by density functional theory simulations. Abstract : MPM‐2 is the first Molecular Porous Material comprised of coordinated AlF6 3− and Al2 F11 5− units. It has a strong sorption preference to C2 H2 and exhibits dynamic breakthrough column separation of C2 H2 from a 1:1 mixture of C2 H2 /CO2 . Efficient C2 H2 separation is enabled by a binding site offering strong electrostatic interactions between C2 H2 and F‐atoms of AlF6 3− moieties as indicated by density functional theory (DFT).